Dynamic task binding for hardware/software reconfigurable networks - Streichert, Thilo; Strengert, Christian; Haubelt, Christian; Teich, Jürgen (In Proceedings of SBCCI 2006, 2006)
In this paper, a new methodology for tolerating link as well as node defects in self-adaptive reconfigurable networks will be presented. Currently, networked embedded systems need a certain level of redundancy for each node and link in order to tolerate defects and failures in a network. Due to monetary constraints as well as space and power limitations, the replication of each node and link is not an option in most embedded systems. Therefore, we will present a hardware/software partitioning algorithm for reconfigurable networks that optimizes the task binding onto resources at runtime such that node/link defects can be handled and data traffic on links between computational nodes will be minimized. This paper presents a new hardware/software partitioning algorithm, an experimental evaluation and for demonstrating the readability, an implementation on a network of FPGA-based boards. Copyright 2006 ACM.
Keywords: Fault-tolerance; Online hardware/software partitioning; Reconfigurable system